2020
DOI: 10.3390/biomedicines8120613
|View full text |Cite
|
Sign up to set email alerts
|

Combined Cell Therapy in the Treatment of Neurological Disorders

Abstract: Cell therapy of neurological diseases is gaining momentum. Various types of stem/progenitor cells and their derivatives have shown positive therapeutic results in animal models of neurological disorders and in clinical trials. Each tested cell type proved to have its advantages and flaws and unique cellular and molecular mechanism of action, prompting the idea to test combined transplantation of two or more types of cells (combined cell therapy). This review summarizes the results of combined cell therapy of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…Indeed, there are reports of a combinatorial approach where the co-transplantation of multiple cell candidates, including MSCs, OECs and NSCs, has been tested in a bid to develop an efficacious cell therapy with synergistic cell properties for SCI repair (62)(63)(64). The outcomes are variable, although on review appear promising as a growing number of studies are following this approach in cell therapy applications for neurological diseases (65). However, a cell candidate that can enhance the key aspects of regeneration including cell survival, engraftment and migration into the lesion and provide neuroprotection may be the most viable strategy.…”
Section: Stem Cell Candidates For Sci Cell Therapymentioning
confidence: 99%
“…Indeed, there are reports of a combinatorial approach where the co-transplantation of multiple cell candidates, including MSCs, OECs and NSCs, has been tested in a bid to develop an efficacious cell therapy with synergistic cell properties for SCI repair (62)(63)(64). The outcomes are variable, although on review appear promising as a growing number of studies are following this approach in cell therapy applications for neurological diseases (65). However, a cell candidate that can enhance the key aspects of regeneration including cell survival, engraftment and migration into the lesion and provide neuroprotection may be the most viable strategy.…”
Section: Stem Cell Candidates For Sci Cell Therapymentioning
confidence: 99%
“…Transplantation of mesenchymal stem cells (MSCs) is a novel approach to the treatment of many severe neurological disorders causing irreversible damage of neural tissue, including traumatic brain injury, spinal cord injury, multiple sclerosis, neurodegenerative diseases, and stroke [ 1 , 2 , 3 ]. In the case of stroke, different routes of MSCs administration, including direct intracerebral, intrathecal, intraventricular, intravenous, intra-arterial, intranasal, and others have been tested in animal studies [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mukai et al focused on clinical trial of the MSC transplantation in the neurological diseases with detailed condition of the clinical trials [ 21 ]. Moreover, Namestnikova et al reported advantages of combinatorial methods, which are combination of coadministration of different stem/progenitor cell types, for the neurological diseases in animal and clinical study [ 22 ]. However, studies on the characteristics of human (hBM-MSCs) before transplantation are very limited.…”
Section: Introductionmentioning
confidence: 99%